Effect of Celery (Apium graveolens L.) Extract Administration on Kidney Function of White Rats (Rattus norvegicus) Wistar Strains Exposed to Lead - Shella Selviana Barus; Ali Napiah Nasution; Wienaldi Wienaldi (International Journal of Health and Pharmaceutical (IJHP), 2024)
Lead significantly affects health because of its sensitivity to the central nervous system and rapid absorption rate. The phytochemicals included in celery, such as flavonoids, may mitigate lead-induced kidney damage. This research aimed to determine how administering celery extract affected the expression of the Caspase-3 gene and the kidney TNF-α gene in Rattus Norvegicus Wistar white rats exposed to lead. The research method true experiment examined the effects of 80 mg/day celery extract on Caspase-3 gene expression and renal TNF-α gene expression in rats exposed to lead. Each of the three groups will include six rats; there will be eighteen male Wistar rats in the study. The study used SPSS 26.0 and the Saphiro Wills test to analyze data on TNF-α and Caspase 3 expression in rats exposed to lead acetate (Pb). The results showed a normal distribution for the negative control group (K-) and the positive control group (K+) and a normal distribution for the treatment group (P). However, the paired t-test showed significant differences in all treatment groups (p <0.05), indicating a normal distribution in the data. The study concludes the impact of celery extract on kidney function in lead-exposed Wistar rats, revealing various active compounds like flavonoids. Despite insignificant caspase 3 reduction, flavonoids showed potential in mitigating lead-induced kidney damage.